Multiparametric Magnetic Resonance Imaging of Prostate Cancer Bone Disease: Correlation With Bone Biopsy Histological and Molecular Features. Issue 2 (February 2018) - Perez-Lopez, Raquel; Nava Rodrigues, Daniel; Figueiredo, Ines; Mateo, Joaquin; Collins, David J.; Koh, Dow-Mu; de Bono, Johann S.; Tunariu, Nina
Abstract : Objectives: The aim of this study was to correlate magnetic resonance imaging (MRI) of castration-resistant prostate cancer (CRPC) bone metastases with histological and molecular features of bone metastases. Materials and Methods: Forty-three bone marrow biopsies from 33 metastatic CRPC (mCRPC) patients with multiparametric MRI and documented bone metastases were evaluated. A second cohort included 10 CRPC patients with no bone metastases. Associations of apparent diffusion coefficient (ADC), normalized b900 diffusion-weighted imaging (nDWI) signal, and signal-weighted fat fraction (swFF) with bone marrow biopsy histological parameters were evaluated using Mann-Whitney U test and Spearman correlations. Univariate and multivariate logistic regression models were analyzed. Results: Median ADC and nDWI signal was significantly higher, and median swFF was significantly lower, in bone metastases than nonmetastatic bone ( P < 0.001). In the metastatic cohort, 31 (72.1%) of 43 biopsies had detectable cancer cells. Median ADC and swFF were significantly lower and median nDWI signal was significantly higher in biopsies with tumor cells versus nondetectable tumor cells (898 × 10 −6 mm 2 /s vs 1617 × 10 −6 mm 2 /s; 11.5% vs 62%; 5.3 vs 2.3, respectively; P < 0.001). Tumor cellularity inversely correlated with ADC and swFF, and positively correlated with nDWI signal ( P < 0.001). In serial biopsies, taken before and after treatment, changes in multiparametric MRI parameters paralleled histological changes. Conclusions: Multiparametric MRI provides valuable information about mCRPC bone metastases. These data further clinically qualify DWI as a response biomarker in mCRPC. Abstract : Supplemental digital content is available in the text.